A method for preparing a dual-activity catalyst based on an alumina framework and its application

Through the dual-active catalyst preparation method based on the alumina framework, the problems of high catalyst cost, short service life and reduced exhaust gas in the prior art are solved, and efficient catalytic conversion of NOX, CO2 and COS are achieved, which significantly improves the efficiency of the catalytic reaction.

CN118788345BActive Publication Date: 2025-03-18JIANGSU JINGJING NEW MATERIALS
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411291732.0
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-09-14
Publication Date
2025-03-18
Estimated Expiration
2044-09-14

AI Technical Summary

Technical Problem

The catalysts used for automotive exhaust purification in the prior art have problems such as high cost, short service life, and reduced exhaust activity against sulfur oxides, and it is difficult to effectively catalyze the degradation of CO2 and COS.

Method used

A dual-active catalyst preparation method based on an alumina framework was used to form a sol with aluminum isopropoxide under acidic conditions by template agent, mesoporous alumina was prepared by sol-gluing method, and Cu/Ni-supported alumina catalyst was prepared by different metal loading methods and pH adjustment methods.

Benefits of technology

The prepared catalyst has high specific surface area, uniform pore size distribution, and good thermal stability. It can efficiently catalyze the conversion rates of NOX, CO2 and COS at low temperatures to reach 99.8%, 99.8% and 99.7%, respectively, which significantly improves the efficiency of the catalytic reaction.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118788345B_ABST
    Figure CN118788345B_ABST
Patent Text Reader

Abstract

The present invention relates to the field of catalyst technology, specifically to a method for preparing a dual-activity catalyst based on an alumina skeleton and its application. The dual-activity catalyst is prepared by loading a metal on mesoporous alumina by a pH adjustment method, and is used in the catalytic reaction of exhaust gas. The present invention controls the amount of template agent, the drying and calcination temperatures, and the pore size of the obtained mesoporous alumina is uniform; the present invention changes the type of template agent and adjusts the reduction temperature to obtain a dual-activity catalyst with a high specific surface area; the present invention controls the mass ratio of copper and nickel and the metal loading to improve the catalytic denitrification efficiency of the dual-activity catalyst; the present invention controls the mass ratio of copper and nickel and the catalytic reaction temperature to increase the conversion rate of the catalytic CO2 methanation reaction of the dual-activity catalyst; the present invention controls the reaction temperature and the catalytic reaction space velocity conditions to improve the COS hydrolysis conversion rate of the dual-activity catalyst.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of catalysts, and in particular to a method for preparing a dual-activity catalyst based on an alumina skeleton and application thereof. Background Art

[0002] With the progress of global industrialization, NOx produced by fixed pollution sources (such as thermal power generation) and mobile air pollution sources is considered to be a major air pollutant. At present, the main technologies for diesel vehicle exhaust purification control include NOx catalytic decomposition technology, three-way catalysis (TWC), NOx storage reduction (NSR) technology, and selective catalytic reduction (SCR) technology. The National VI emission standard promulgated and implemented on July 1, 2020 is more stringent than the National V standard in the NOx emission standard for diesel vehicle exhaust. Vanadium-based catalysts are more commonly used in the National V stage, and their low-temperature window characteristics are narrow, which cannot meet the National VI and Euro VI emission standards.

[0003] Patent CN201780032379.6 reports a CHA-type zeolite and a method for manufacturing the same. N,N,N-trialkyladamantyl ammonium salt and N,N,N-trialkylcyclohexyl ammonium salt are used as composite templates to synthesize a CHA-type zeolite having a molar ratio of silica to alumina of 10.0 to 55.0. The zeolite can be used as an SCR catalyst for NOx catalytic denitrification reaction, indicating that obtaining a catalyst with good thermal stability and good dispersion of loaded metals is the preferred solution.

[0004] However, the N,N,N-trialkyl-1-adamantyl ammonium salts and their alkaline compounds used as templates in the prior art are expensive, have low utilization rates, are difficult to recycle, and are prone to pollution. In addition, this conventionally synthesized CHA molecular sieve will significantly reduce the activity of the SCR catalyst in exhaust gas containing sulfur oxides. Therefore, a template with low cost, easy post-processing and strong structure-directing ability is needed to synthesize an SCR catalyst with a large specific surface area, a large pore volume and good thermal stability.

[0005] The gases released by automobile exhaust contain hundreds of different compounds, among which pollutants include solid suspended particles, carbon monoxide, carbon dioxide, hydrocarbons, nitrogen oxides, lead and sulfur oxides. In addition to NOx pollution, serious pollution also includes CO2 and COS gases. Although CO2 and COS can be absorbed by plants and irreversibly degraded under the action of plants, the rapid development of industrialization and urbanization has led to a large amount of anthropogenic CO2 and COS emissions. If these exhaust gases are not catalytically eliminated, long-term and large-scale emissions can form sulfate aerosol particles through chemical reactions in the stratosphere and troposphere, which will have an adverse effect on the Earth's atmospheric radiation intensity, ozone depletion and global climate change.

[0006] The document A. Achour, Tuning of catalytic activity by thermoelectric materials for carbon dioxide hydrogenation, Advanced Energy Materials (2018) discloses the thermoelectric catalytic effect of the thermoelectric material BiCuSeO on the CO2 reduction reaction. It is found that the thermoelectric effect can not only increase the reaction rate, but also change the chemical equilibrium and affect the product selection, and finally realize the conversion of CO2 to CO and H2O, and the product has high CO selectivity; however, the BiCuSeO thermoelectric catalytic material prepared in the document is a bulk material, and the effective contact area with the CO2 waste gas is small, which greatly limits the catalytic reaction efficiency. At the same time, the conversion of CO2 to CO and H2O is realized, and the generated CO still needs to be further processed, and a catalyst for the methanation of carbon dioxide needs to be developed.

[0007] Patent CN200410042862.7 reports a COS and CS2 hydrolysis catalyst and its application. By loading ammonium salt onto γ-Al2O3 to catalyze the hydrolysis of organic sulfur, this method can effectively improve the removal accuracy of organic sulfur, and the loaded components are cheap and easy to obtain; however, this method introduces more ammonium salts in the preparation, causing ammonia nitrogen pollution during the preparation and use process. In addition, this method cannot solve the service life problem of the hydrolysis catalyst well, and it is very easy to lose activity, affecting the use effect.

[0008] Alumina is a white, tasteless, crystalline substance that is insoluble in water, odorless, tasteless, and easy to absorb moisture without deliquescing. It exists in nature in the form of various minerals such as bauxite and corundum. Due to its excellent physical and chemical properties, alumina is widely used in catalysis. Alumina has a phenomenon of isomorphism, with more than 10 crystal forms. The change of crystal structure is mainly achieved by regulating the roasting temperature. At present, γ-Al2O3, α-Al2O3, and β-Al2O3 are widely used in industry. Among them, γ-Al2O3 has a higher specific surface area and better surface acidity and alkalinity, and is most widely used in the field of catalysis.

[0009] In summary, in the prior art, the waste gas in automobile exhaust is mainly treated by adsorption and environmental metabolism. However, with the development of technology and the increase of human activities, the emission volume is gradually increasing. For the catalytic degradation of waste gas, certain industrial methods need to be adopted. The molecular sieve modified by using N,N,N-trialkyl-1-adamantyl ammonium salt and its alkaline compound as template has certain catalytic effect, but the cost of use is high, and the low specific surface area affects the catalytic activity; loading ammonium salt on γ-Al2O3 can catalyze the hydrolysis of organic sulfur, but the large-scale use of ammonium salt is very likely to cause ammonia nitrogen pollution, and the service life is reduced. Therefore, it is necessary to synthesize an active catalyst with a large specific surface area, average pore size and good thermal stability by using a template with low cost, easy post-processing and strong structure-directing ability.

[0010] To this end, a method for preparing a dual-activity catalyst based on an alumina framework and its application are proposed. Summary of the invention

[0011] The object of the present invention is to provide a method for preparing a dual-activity catalyst based on an alumina skeleton and its application. The method comprises the following steps: using a template agent to form a sol with aluminum isopropoxide under acidic conditions, and using a sol-gel method to prepare mesoporous alumina. The prepared mesoporous alumina has an average pore size of 6 nm, a pore volume of 0.41 cm³ / g, and a uniform pore size distribution; by changing the type of the template agent, the specific surface area of ​​the mesoporous alumina is controlled, and by using different metal loading methods and adjusting the reduction temperature, the specific surface area of ​​the prepared Cu / Ni loaded alumina is 335.4 m² / g, and the specific surface area is improved; copper salt and nickel salt are reduced and calcined by a pH adjustment method to prepare a Cu / Ni loaded alumina catalyst, which is used for catalytic denitration reaction, and the Cu / Ni mass ratio and the metal loading amount are controlled to prepare a Cu / Ni loaded alumina catalyst NO X The conversion rate is 99.8%; the Cu and Ni metals are loaded into the pores of mesoporous alumina by the pH adjustment method, and the obtained catalyst is used in the methanation reaction of carbon dioxide. By controlling the mass ratio of Cu and Ni and the catalytic temperature, the CO2 conversion rate of the obtained Cu / Ni loaded alumina catalyst is 99.8%; by controlling the mass ratio of Cu and Ni, the reaction temperature and the space velocity, the obtained Cu / Ni loaded alumina catalyst has a COS hydrolysis conversion rate of 99.7%.

[0012] To achieve the above object, the present invention provides the following technical solutions:

[0013] In one aspect, the present invention provides a method for preparing a dual-activity catalyst based on an alumina framework, wherein the dual-activity catalyst comprises mesoporous alumina and a metal salt:

[0014] The preparation method of the mesoporous alumina comprises the following steps:

[0015] The template agent is added to ethanol, and stirred at 200 rpm for 10 minutes to fully dissolve it to obtain a solution; an acid regulator is added to the solution, the pH is adjusted to 0.28-0.42, and the mixture is evenly mixed to obtain an acidic solution; aluminum isopropoxide is added to the acidic solution, and the solution is placed in an ultrasonic cleaner to fully dissolve it to obtain a sol; the sol is placed in a vacuum drying oven at 60-90° C. and dried for 24 hours to obtain a dry material; the dry material is ground into powder, and after grinding, the powder is placed in a box-type resistance furnace and heated to 400-700° C., and the powder is calcined at a constant temperature for 6 hours, and then cooled to room temperature to obtain the mesoporous alumina;

[0016] The dual-activity catalyst is prepared by a pH adjustment method, and the preparation method comprises the following steps:

[0017] Dissolving a metal salt in an ammonia solution to obtain a metal salt solution; adjusting the pH value of the mixed solution of the metal salt solution to 12 using concentrated ammonia water to obtain an alkaline solution; adding the mesoporous alumina to the alkaline solution, placing it in an oscillator and oscillating it at room temperature for 2 hours to obtain a mixture; washing and filtering the mixture for multiple times, and vacuum drying it at 100° C. for 12 hours to obtain a dry body; reducing the dry body with a reducing gas at a flow rate of 50 mL / min, a temperature of 550° C., and a time of 8 hours to obtain the dual-activity catalyst;

[0018] The mass ratio of the template to aluminum isopropoxide is 1:4;

[0019] The template is selected from silicon-containing templates;

[0020] The silicon-containing template is synthesized by emulsifying butyl methacrylate, KH-570 and tetradecyl acrylate to initiate polymerization;

[0021] The mass ratio of the metal in the dual-activity catalyst to the mesoporous alumina is 0.001-0.007:1;

[0022] The acid regulator is selected from nitric acid;

[0023] The metal salt is selected from a mixture of copper nitrate and nickel chloride; the mass ratio of the copper nitrate to the nickel chloride is 1-3:1-3.

[0024] Preferably, the dual-activity catalyst is used in a catalytic reaction of exhaust gas, wherein the catalytic reaction of exhaust gas includes catalytic denitration reaction, carbon dioxide methanation reaction, and COS hydrolysis catalysis; in the catalytic denitration reaction, the metal salt is selected from a mixture of copper nitrate and nickel chloride in a mass ratio of 2:1; the metal loading is 0.5%; and the reaction temperature is 300°C.

[0025] Preferably, in the carbon dioxide methanation reaction, the metal salt is selected from the copper nitrate and the nickel chloride mixed in a mass ratio of 1:2; the metal loading is 0.5%; and the reaction temperature is 350°C.

[0026] Preferably, in the COS hydrolysis catalysis, the metal salt is selected from the copper nitrate and the nickel chloride mixed in a mass ratio of 1:1; the metal loading is 0.5%; the reaction temperature is 80° C., and the space velocity is 8000 / h.

[0027] Compared with the prior art, the present invention has the following beneficial effects:

[0028] 1. The present invention uses a template to form a sol with aluminum isopropoxide under acidic conditions, and uses a sol-gel method to prepare mesoporous alumina. After the template is dissolved, it is heated in H + Under the action of 3+ A synergistic effect occurs to form a liquid crystal phase. High-temperature calcination removes the template agent, increases the formation of alumina surface agglomerates, and increases the surface area of ​​alumina. By controlling the pH value, the amount of template agent, the drying temperature, and the calcination temperature, the average pore size of the mesoporous alumina is 6nm, the pore volume is 0.41cm³ / g, and the pore size distribution is uniform. When used in the exhaust gas catalytic reaction, it is beneficial to the flow of the product gas and increases the exhaust gas catalytic yield.

[0029] 2. The present invention controls the specific surface area of ​​mesoporous alumina by changing the type of template agent, and utilizes the siliceous part in the silicon-containing template agent to first enter the crystallized isopropanol aluminum skeleton, and the other end forms an organic layer to directly guide the formation of the mesoporous structure. In addition, the organic tail of the organosilane is attached to the surface of the nanocrystal, which limits the further growth of the alumina nanocrystals, thereby forming cubic agglomerates with certain gaps, increasing the specific surface area of ​​the mesoporous alumina, and at the same time using different metal loading methods to adjust the reduction temperature, the specific surface area of ​​the obtained Cu / Ni loaded alumina is 335.4m2 / g, the specific surface area is increased, the catalytic reaction sites are increased, and the catalytic efficiency is improved.

[0030] 3. The present invention uses a pH adjustment method to reduce and roast copper salt and nickel salt to obtain a Cu / Ni loaded alumina catalyst, and uses it to catalyze the denitration reaction. Under low temperature conditions, copper has excellent adsorption capacity for NO, making the NO oxidation ability stronger. The introduction of Ni metal can provide reduction sites, and Cu / Ni synergistically makes NO X The dual-activity catalyst NO was converted into harmless nitrogen and water by controlling the mass ratio of Cu and Ni and the metal loading. X The conversion rate was 99.8%, showing a significantly improved catalytic denitrification efficiency.

[0031] 4. The present invention utilizes a pH adjustment method to load Cu and Ni metals into the pores of mesoporous alumina, and the obtained catalyst is applied to the carbon dioxide methanation reaction to increase the carbon dioxide conversion rate; since CO2 methanation is an exothermic reaction, untimely heat dissipation will lead to the formation of hot spots on the catalyst, thereby causing sintering of the active component nickel and reducing the CO2 conversion rate. At the same time, the synergistic reduction performance of Cu metal and Ni metal is utilized to control the Cu, Ni mass ratio and the catalytic temperature, and the CO2 conversion rate of the obtained dual-activity catalyst is 99.8%, showing a significantly improved carbon dioxide methanation reaction conversion rate.

[0032] 5. The present invention utilizes a pH adjustment method to load Cu and Ni metals into the pores of mesoporous alumina, utilizes the alkaline groups on the surface of mesoporous alumina to adsorb COS molecules, controls the mass ratio of Cu and Ni metals to catalyze the reaction between COS molecules and water molecules, and accelerates the COS hydrolysis conversion rate; since too low a temperature is not conducive to the movement of H2S molecules in the pores of mesoporous alumina, and high temperature is not conducive to the desorption of H2S molecules, the reaction temperature and the catalytic reaction space velocity conditions are controlled to obtain a dual-activity catalyst with a COS hydrolysis conversion rate of 99.7%, showing a significantly improved carbonyl sulfide hydrolysis conversion performance. BRIEF DESCRIPTION OF THE DRAWINGS

[0033] Figure 1 is a pore size distribution diagram of the mesoporous alumina prepared in Example 13;

[0034] Figure 2 This is the SEM image of Cu / Ni loaded alumina prepared in Example 25. DETAILED DESCRIPTION

[0035] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0036] If the specific conditions are not specified in the examples, the experiments were carried out under conventional conditions or conditions recommended by the manufacturer. If the manufacturers of the reagents or instruments are not specified, they are all conventional products that can be purchased commercially.

[0037] The P123 described in the present invention is a polyethylene oxide-polypropylene oxide-polyethylene oxide triblock copolymer.

[0038] The CAS number of the butyl methacrylate in the present invention is 97-88-1.

[0039] See also Figure 1 to Figure 2The present invention provides a method for preparing a dual-activity catalyst based on an alumina skeleton and its application, and the technical scheme is as follows:

[0040] Examples 1-18

[0041] Preparation of mesoporous alumina:

[0042] The template agent polyethylene oxide-polypropylene oxide-polyethylene oxide triblock copolymer is added to 40 ml of ethanol according to the mass ratio of the template agent to aluminum isopropoxide of 1:2-6, and stirred at 200 rpm for 10 minutes to fully dissolve it to obtain a solution; an acid regulator is added to the solution, the pH is adjusted to 0.28-0.42, and the mixture is evenly mixed to obtain an acidic solution; 10 g of aluminum isopropoxide is added to the acidic solution, and the solution is placed in an ultrasonic cleaner for ultrasonic dissolution to obtain a sol; the sol is placed in a vacuum drying oven at 60-90° C. and dried for 24 hours to obtain a dry material; the dry material is ground into powder, and after grinding, it is placed in a box-type resistance furnace and heated to 400-700° C. at a heating rate of 5° C. per minute, and calcined at a constant temperature for 6 hours, and naturally cooled to room temperature in the furnace to obtain mesoporous alumina; the specific preparation conditions and parameters are shown in Table 1.

[0043] Table 1 Component dosage of Examples 1-18

[0044] Example Template and aluminum isopropoxide mass ratio Types of acid regulators pH Drying temperature / ℃ Calcination temperature / ℃ Example 1 1:2 Nitric acid 0.35 70 500 Example 2 1:3 Nitric acid 0.35 70 500 Example 3 1:4 Nitric acid 0.35 70 500 Example 4 1:5 Nitric acid 0.35 70 500 Example 5 1:6 Nitric acid 0.35 70 500 Example 6 1:4 hydrochloric acid 0.35 70 500 Example 7 1:4 sulfuric acid 0.35 70 500 Example 8 1:4 Phosphoric acid 0.35 70 500 Example 9 1:4 Nitric acid 0.28 70 500 Example 10 1:4 Nitric acid 0.32 70 500 Embodiment 11 1:4 Nitric acid 0.38 70 500 Example 12 1:4 Nitric acid 0.42 70 500 Embodiment 13 1:4 Nitric acid 0.35 60 500 Embodiment 14 1:4 Nitric acid 0.35 80 500 Embodiment 15 1:4 Nitric acid 0.35 90 500 Example 16 1:4 Nitric acid 0.35 60 400 Embodiment 17 1:4 Nitric acid 0.35 60 600 Embodiment 18 1:4 Nitric acid 0.35 60 700

[0045] Comparative Example 1 The preparation method and parameter conditions are the same as those of Example 1, except that no template is added.

[0046] Comparative Example 2 is different from Example 1 in that commercial alumina was used.

[0047] Example 19: Pore diameter and pore volume test

[0048] The aluminum oxide materials prepared in Examples 1-18 and Comparative Examples 1-2 were analyzed using a fully automatic surface area and porosity analyzer (BET) model ASAP-2460-3.01 at 77K. The samples were measured using the 77K N2 static adsorption method, and the test method was the low-temperature nitrogen adsorption method. The samples were vacuum degassed at 200°C for 8 hours before adsorption. The vacuum degree of the sample chamber was in the range of P / P0=0-1, where P0 was one atmosphere. The BJH model was used to calculate the average and pore volume, and the BET method was used to calculate the specific surface area; the test results are shown in Table 2, and the pore size distribution of Example 13 is shown in Table 2. Figure 1 shown.

[0049] Table 2 Test results of Examples 1-18 and Comparative Examples 1-2

[0050] Example Specific surface area / m² / g Pore ​​volume / cm³ / g Average pore size / nm Example 1 328.2 0.40 8 Example 2 325.8 0.41 7 Example 3 324.6 0.43 7 Example 4 323.5 0.42 10 Example 5 322.7 0.42 12 Example 6 322.8 0.41 8 Example 7 322.5 0.45 9 Example 8 322.6 0.42 12 Example 9 322.5 0.43 12 Example 10 324.2 0.41 10 Embodiment 11 323.5 0.42 8 Example 12 321.6 0.42 12 Embodiment 13 323.8 0.41 6 Embodiment 14 323.8 0.45 10 Embodiment 15 323.6 0.48 12 Example 16 318.7 0.40 7 Embodiment 17 322.6 0.41 6 Embodiment 18 322.8 0.43 7 Comparative Example 1 196.4 0.39 14 Comparative Example 2 175.2 0.38 22

[0051] From the results in Table 1, it can be seen that the specific surface area and average pore size of the alumina prepared without adding the template in Comparative Example 1 are significantly increased compared with Examples 1-18. The addition of the template can play a "pore-forming" role in the synthesis of the mesoporous material, increasing the specific surface area of ​​the material while improving the particle size distribution of the material; the specific surface area of ​​Comparative Example 2 is equivalent to that of Comparative Example 1, which further verifies the "pore-forming" effect of the template; from the results of Examples 1-5, it can be seen that with the reduction of the amount of the template, the specific surface area of ​​the material has a slight downward trend, but with the reduction of the amount, the average pore size gradually increases, and the particle size distribution in the mesoporous material is uneven; due to the template being dissolved in H + Under the action of 3+ A synergistic effect occurs to form a liquid crystal phase. However, when the amount of template agent is too much, the pore size distribution is uniform, but it will cause the micelles to aggregate excessively, which is not conducive to the formation of the pore template and the number of pores is reduced; as the amount of template agent is reduced, the utilization rate of the template agent is higher, which is conducive to the formation of more template pores, thereby increasing the reaction active sites and improving the catalytic efficiency of the material. However, too little template agent makes the isopropanol aluminum less in contact with the template agent, resulting in a reduction in pore size, uneven pore size distribution, and an increase in the average pore size; from the results of Example 1 and Examples 6-8, it can be seen that the change in the type of acid regulator has little effect on the specific surface area and pore volume, but phosphoric acid is weak in acidity, and the increase in dosage under the same pH conditions further shows an increase in the average pore size, uneven pore size distribution, and reduced catalytic efficiency; from the results of Examples 1 and Examples 9-12, it can be seen that with the increase in pH value, the average pore size shows a trend of first decreasing and then increasing, due to the interaction between the template agent and Al 3+ The liquid crystal phase is formed by adjusting the pH value to cause precipitation. + and Al 3+ can synergize with the template, so when the pH value is low, H + With Al 3+ Together they cover the surface of the colloid bundles, and the two compete and synergize to reduce the aggregation of the colloid bundles, resulting in fewer agglomerates on the surface of alumina after the template is removed, a decrease in specific surface area, and an increase in average pore size; when the pH is maintained at 0.32-0.35, the agglomerates on the surface of the material can be increased, the specific surface area can be increased, and the reaction sites of the catalyst can be increased; the results of Examples 1 and 13-15 show that with the increase of drying temperature, the pore volume of mesoporous alumina increases, the macroporous structure also gradually increases, the number of mesoporous structures decreases, and the average pore size increases; the results of Examples 1 and 16-18 show that the change in calcination temperature has little effect on the pore volume and average pore size of mesoporous alumina. Comprehensive Table 2 and Figure 1The results showed that when the mass ratio of template to aluminum isopropoxide was 1:4, the pH was 0.35, the drying temperature was 60℃, and the calcination temperature was 500℃, the average pore size of the prepared mesoporous alumina was 6nm, the pore volume was 0.41cm³ / g, and the pore size distribution was uniform.

[0052] Embodiment 20

[0053] Preparation of dual-activity catalyst by equal volume impregnation method:

[0054] Dissolve copper nitrate in 100 ml of ammonia solution to obtain a metallic copper solution; dissolve nickel chloride hexahydrate in 100 ml of ammonia solution to obtain a metallic nickel solution; mix the metallic copper solution and the nickel chloride hexahydrate under stirring to obtain a mixed solution; dilute 0.05 ml of the mixed solution with water to 1.5 ml to obtain a diluted metal solution; drop the diluted metal solution into 2.0 g of the mesoporous alumina obtained in Example 13, stir and mix with a glass rod to obtain a mixed solution, and ultrasonicate the mixed solution at an ultrasonic power of 200 W and an ultrasonic time of 2 h to promote uniform distribution of the metal precursor in the pores of the carrier to obtain a mixed solution. The invention relates to a method for preparing a double-active catalyst, wherein the catalyst comprises the steps of: placing the mixture at 25°C for 2 hours, placing the mixture in an 80°C forced air drying oven and drying it for 12 hours to obtain a dry product; transferring the dry product to a muffle furnace for calcination at a heating rate of 1°C / min, a calcination temperature of 400°C, a calcination time of 4 hours, and naturally cooling the product to room temperature after calcination to obtain a calcined product; reducing the calcined product by a reducing gas (the reducing gas is composed of H2 and N2, wherein the volume proportion of hydrogen is 20%) at a flow rate of 50 mL / min, a reduction temperature of 550°C, and a reduction time of 8 hours to obtain a dual-active catalyst, wherein the mass ratio of Cu to Ni in the catalyst is 1:1, and the metal loading is 0.5%.

[0055] Embodiment 21

[0056] Preparation of dual-activity catalyst by co-precipitation method:

[0057] Dissolve copper nitrate in 100 ml of ammonia solution to obtain a metallic copper solution; dissolve nickel chloride hexahydrate in 100 ml of ammonia solution to obtain a metallic nickel solution; mix the metallic copper solution and the nickel chloride hexahydrate under stirring to obtain a mixed solution; drop the mixed solution into 2.0 g of the mesoporous alumina obtained in Example 13, stir and mix thoroughly with a glass rod to obtain a mixture; dissolve NaOH (375 mmol) in 150 mL of deionized water to prepare a 10% NaOH solution; drop the NaOH solution into the mixture dropwise, stir vigorously, and separate and centrifuge the generated solid precipitate, filter and wash it. The method comprises the steps of: washing the precipitate; drying the precipitate in an 80°C forced air drying oven for 12 hours to obtain a dry solid; transferring the dry solid to a muffle furnace for calcination at a heating rate of 1°C / min, a calcination temperature of 400°C, a calcination time of 4 hours, and naturally cooling to room temperature after calcination to obtain a calcined product; reducing the calcined product by a reducing gas (the reducing gas is composed of H2 and N2, wherein the volume proportion of hydrogen is 20%) at a flow rate of 50 mL / min, a reduction temperature of 550°C, and a reduction time of 8 hours to obtain the dual-activity catalyst, wherein the mass ratio of Cu to Ni in the catalyst is 1:1, and the metal loading is 0.5%.

[0058] Embodiment 22

[0059] The dual-activity catalyst was prepared by pH adjustment method:

[0060] Dissolve copper nitrate in 100 ml of an ammonia solution to obtain a metallic copper solution; dissolve nickel chloride hexahydrate in 100 ml of an ammonia solution to obtain a metallic nickel solution; mix the metallic copper solution and the metallic nickel solution evenly under stirring to obtain a mixed solution; adjust the pH value of the mixed solution to 12 using concentrated ammonia water to obtain an alkaline solution; add 2 g of the mesoporous alumina prepared in Example 13 to the alkaline solution, place it in an oscillator and oscillate at room temperature for 2 hours to obtain a mixture; wash and filter the mixture several times, and vacuum dry it at 100°C for 12 hours to obtain a dry body; reduce the dry body by reducing gas at a flow rate of 50 mL / min (the reducing gas is composed of H2 and N2, wherein the volume proportion of hydrogen is 20%), the reduction temperature is 550°C, and the reduction time is 8 hours to obtain the dual-activity catalyst, wherein the mass ratio of Cu and Ni in the catalyst is 1:1, and the metal loading is 0.5%.

[0061] Embodiment 23

[0062] Preparation of silicon-containing template:

[0063] 0.2 g of potassium persulfate was dissolved in 20 ml of deionized water to prepare a potassium persulfate solution; 500 ml of deionized water was added to a three-necked flask, the temperature was raised to 70° C., and the flask was replaced with nitrogen to prepare a heating system; 50 ml of butyl methacrylate, 15 ml of KH-570, and 5 ml of tetradecyl acrylate were added to the heating system respectively, and 10% of the potassium persulfate solution was slowly added, stirred evenly, and reacted at 70° C. for 1 hour to prepare a mixed system; 5% of sodium dodecyl sulfate was added to the mixed system as an emulsifier, and stirring was continued for 2 hours to prepare a white latex; the white latex was transferred to a mold, washed, and vacuum dried at 80° C. for 2 hours to prepare a silicon-containing template.

[0064] The dual-activity catalyst was prepared according to the preparation method and parameter conditions of Example 22.

[0065] Examples 24-29 were prepared according to the preparation method and parameter conditions of Example 22, with the differences shown in Table 3.

[0066] Comparative Example 3 The preparation was carried out according to the preparation method and parameter conditions of Example 22, except that sodium borohydride was used for reduction.

[0067] Example 30 Specific surface area test

[0068] The metal-supported alumina catalysts prepared in Examples 20-29 and Comparative Example 3 were measured using a fully automatic specific surface area and porosity analyzer (BET) model ASAP-2460-3.01, using a 77K N2 static adsorption method, and the test method was a low-temperature nitrogen adsorption method. Before adsorption, the sample was vacuum degassed at 200°C for 8 hours, and the vacuum degree of the sample chamber was within the range of P / P0=0-1, where P0 was one atmosphere. The specific surface area was calculated using the BET method; the test results are shown in Table 3.

[0069] Table 3 Test results of Examples 20-29 and Comparative Example 3

[0070] Example Template Type Preparation method of metal-loaded alumina Reduction temperature / ℃ Specific surface area / m² / g Embodiment 20 P123 Equal volume impregnation method 550 284.5 Embodiment 21 P123 Coprecipitation 550 268.6 Embodiment 22 P123 pH adjustment method 550 305.4 Embodiment 23 Sodium dodecyl sulfate pH adjustment method 550 276.5 Embodiment 24 Hexadecyltrimethylammonium bromide pH adjustment method 550 296.5 Embodiment 25 Silicon-containing template pH adjustment method 550 335.4 Embodiment 26 Silicon-containing template pH adjustment method 400 298.6 Embodiment 27 Silicon-containing template pH adjustment method 500 312.4 Embodiment 28 Silicon-containing template pH adjustment method 600 325.2 Embodiment 29 Silicon-containing template pH adjustment method 650 306.5 Comparative Example 3 Silicon-containing template pH adjustment method / 245.8

[0071] The results in Table 3 show that the selection of the template has a great influence on the specific surface area of ​​the metal-loaded alumina catalyst. Comparing Examples 22-25, the specific surface area of ​​the alumina prepared using the cationic active agent is significantly improved relative to that of sodium dodecyl sulfate. Since the mesoporous material prepared by sodium dodecyl sulfate has poor stability, the structure collapses during the high-temperature baking reduction process, resulting in a decrease in the specific surface area. The silicon-containing template is formed by copolymerizing methyl methacrylate with KH-570 under the action of an initiator. The siliceous part of the template first enters the crystallized aluminum isopropoxide skeleton. , an organic layer is formed at the other end to directly guide the formation of a mesoporous structure. In addition, the organic tail of the organosilane is attached to the surface of the nanocrystal, which limits the further growth of the alumina nanocrystals, thereby forming a cubic agglomerate with certain gaps, maintaining a high specific surface area while controlling the formation of mesopores through hydrogen bonds, surface adsorption and other forces; Comparative Examples 20-22 show that the methods of metal-loaded mesoporous alumina are different, which has a greater impact on the specific surface area of ​​the material. The metal-loaded alumina prepared by the pH adjustment method has a higher specific surface area. During the reduction of the catalytic gas, the movement speed of the reducing gas on the catalyst surface will be accelerated, and the catalytic efficiency of the catalyst will be improved. In addition, by precisely controlling the pH value of the catalyst system, the metal ions and the mesoporous alumina form a strong electrostatic bond and are anchored on the carrier surface. After reduction, a metal-loaded alumina catalyst with high dispersibility, small particle size and narrow size distribution is formed; Since the size of the metal particles of the loaded catalyst prepared by the impregnation method cannot be adjusted, large-sized metal particles will occupy the pore size of the alumina, the specific surface area of ​​the catalyst is reduced, and the catalytic efficiency is reduced; Through the results of Examples 25-29, it can be seen that with the reduction temperature When the reduction temperature is lower than 550°C, the metal particles reduced are less, and the metal oxides occupy the alumina pores, which reduces the specific surface area of ​​the catalyst and further reduces the catalytic efficiency; when the reduction temperature is too high, the metal oxides agglomerate significantly, resulting in a decrease in the conversion rate, and the agglomerated oxides occupy the alumina pores, reducing the specific surface area; in Comparative Example 3, sodium borohydride reduction cannot fully reduce the metal oxides, and inorganic components are introduced into the mesoporous alumina, which reduces the specific surface area of ​​the material and affects the catalytic efficiency. It can be seen from the results of Table 3 that the mesoporous alumina is prepared using a silicon-containing template, and the metal loading method and the reduction temperature are controlled at the same time. The specific surface area of ​​the obtained dual-activity catalyst is 335.4m² / g, which has a significantly improved specific surface area.

[0072] Embodiment 31

[0073] 12.4 mg of copper nitrate is dissolved in 100 ml of ammonia solution to obtain a metallic copper solution; 18.5 mg of nickel chloride hexahydrate is dissolved in 100 ml of ammonia solution to obtain a metallic nickel solution; the metallic copper solution and the metallic nickel solution are mixed evenly, and the pH value of the mixed solution is adjusted to 12 with concentrated ammonia water to obtain an alkaline solution; 2 g of the mesoporous alumina prepared in Example 25 is added to the alkaline solution, and the mixture is placed in an oscillator and oscillated at room temperature for 2 hours to obtain a mixture; the mixture is washed and filtered for multiple times, and vacuum dried at 100°C for 12 hours to obtain a dry body; the dry body is reduced by a reducing gas with a flow rate of 50 mL / min (the reducing gas is composed of H2 and N2, in which the volume proportion of hydrogen is 20%), the reduction temperature is 550°C, and the reduction time is 8 hours to obtain a dual-activity catalyst, in which the mass ratio of Cu and Ni in the catalyst is 1:1, and the metal loading is 0.5%.

[0074] Examples 32-44 were prepared according to the preparation method and parameter conditions of Example 31, with the differences as shown in Table 4.

[0075] Comparative Example 4 The preparation method and parameter conditions of Example 31 were referred to, except that only Cu-loaded alumina was used.

[0076] Example 45 Catalytic Denitrification Reaction

[0077] The metal-supported alumina catalyst prepared in Examples 32-44 and Comparative Example 4 was loaded into a reactor and contained a mixed gas flow of 160 mL / min containing 500 ppm NO, 500 ppm NH3, 10% by volume O2, 5% by volume water vapor and Ar as the balance gas, passed through a preheater (set to 250°C) and then entered the SCR reactor. The examples were tested at a reaction temperature of 150 to 450°C and a gas hourly space velocity based on a volume of 48,000 / h; NO conversion or "de-NO x The activity was measured under steady-state conditions by using a Bruker EQUINOX 55 FT-IR spectrometer to measure the NO x , NH3 and N2O concentrations, and the conversion rate is calculated as follows.

[0078] NO X Conversion rate = NO X Inlet concentration - NO X Outlet concentration / NO X Inlet concentration × 100%; test results are shown in Table 4.

[0079] Table 4 Catalytic denitration test of Examples 31-44 and Comparative Example 4

[0080] Example Metal salt type Metal salt mass ratio Metal loading Reaction temperature / ℃ <![CDATA[NO X Conversion rate / %]]> Embodiment 31 Copper nitrate + nickel chloride 1:1 0.5% 300 98.5 Embodiment 32 Copper nitrate + ferric chloride 1:1 0.5% 300 97.6 Embodiment 33 Copper nitrate + zinc chloride 1:1 0.5% 300 95.2 Embodiment 34 Nickel chloride + ferric chloride 1:1 0.5% 300 97.4 Embodiment 35 Copper nitrate + nickel chloride 1:2 0.5% 300 96.2 Embodiment 36 Copper nitrate + nickel chloride 2:1 0.5% 300 99.8 Embodiment 37 Copper nitrate + nickel chloride 3:1 0.5% 300 99.6 Embodiment 38 Copper nitrate + nickel chloride 2:1 0.1% 300 88.1 Embodiment 39 Copper nitrate + nickel chloride 2:1 0.3% 300 92.5 Embodiment 40 Copper nitrate + nickel chloride 2:1 0.7% 300 98.2 Embodiment 41 Copper nitrate + nickel chloride 2:1 0.5% 150 82.8 Embodiment 42 Copper nitrate + nickel chloride 2:1 0.5% 200 90.6 Embodiment 43 Copper nitrate + nickel chloride 2:1 0.5% 400 99.5 Embodiment 44 Copper nitrate + nickel chloride 2:1 0.5% 450 99.6 Comparative Example 4 Copper nitrate / 0.5% 300 95.2

[0081] The results in Table 4 show that the conversion rate of catalytic denitration by the Cu-loaded alumina catalyst prepared by the pH adjustment method using only copper nitrate as the metal salt in Comparative Example 4 is significantly lower than that of the alumina loaded with multiple metals in Examples 31-44; the results in Examples 31-34 show that the introduction of Ni and Fe metals using nickel chloride and ferric chloride can improve the conversion rate of NOx and enhance the purification capacity of exhaust gas. In Example 31, copper nitrate and nickel chloride are used in combination, and the Cu / Ni-loaded alumina prepared has more prominent NO X The results of Example 31 and Example 35-37 show that as the Cu content increases, NO X The conversion rate gradually increases and remains unchanged. Under low temperature conditions, copper has excellent adsorption capacity for NO, making NO oxidation more powerful. The introduction of Ni metal can provide reduction sites, which cooperates with copper metal to make NO X It can be seen from the results of Examples 31 and 38-40 that as the metal loading increases, NO X The conversion rate shows a trend of increasing first and then decreasing. Excessive metal particles are loaded in the pores of alumina, which reduces the gas flowability. The generated nitrogen and water adhere to the pores of alumina, reducing the conversion rate. By comparing the results of Example 31 and Examples 41-44, it can be seen that as the reaction temperature increases, NO X The conversion rate gradually increased and then decreased. The high temperature gradually destroyed the stability of the metal particles, causing agglomeration between the particles and reducing the conversion rate. According to the results in Table 4, the dual-activity catalyst prepared by using copper nitrate + nickel chloride has a high conversion rate of NO at 300 °C. X The conversion rate was 99.8%, showing a significantly improved catalytic denitrification efficiency.

[0082] Examples 45-54 The preparation methods and parameter conditions of the reference examples are shown in Table 5.

[0083] Comparative Example 5 The preparation method and parameter conditions of Example 31 were referred to, except that only Ni-loaded alumina was used.

[0084] Example 55 Carbon dioxide methanation reaction performance

[0085] The activity test of carbon dioxide methanation reaction was carried out in a fixed bed reactor at atmospheric pressure. 60 mg of catalyst was evenly mixed with 120 mg of quartz sand and fixed in the reaction tube with quartz wool. In the activity test, the mixed gas flow rate was adjusted to 40 mL / min, and the molar ratio of H2:CO2:N2 was 72:24:8. The test temperature range was 200-600 °C, and a point was sampled every 50 °C, and each temperature point was stabilized for 40 minutes; the reaction performance was tested by CO2 conversion rate; the CO2 conversion rate test results are shown in Table 5.

[0086] X CO2 =CO 2进 -CO 2出 / CO 2进 ×100%

[0087] Table 5 Performance test of carbon dioxide methanation reaction of Examples 45-54 and Comparative Example 4

[0088] Example Metal salt type Metal salt mass ratio Metal loading Reaction temperature / ℃ <![CDATA[CO2 conversion rate / %]]> Embodiment 31 Copper nitrate + nickel chloride 1:1 0.5% 350 56.8 Embodiment 45 Copper nitrate + magnesium chloride 1:1 0.5% 350 50.4 Embodiment 46 Nickel chloride + magnesium chloride 1:1 0.5% 350 55.2 Embodiment 47 Copper nitrate + zinc chloride 1:1 0.5% 350 48.5 Embodiment 48 Nickel chloride + zinc chloride 1:1 0.5% 350 51.4 Embodiment 49 Copper nitrate + nickel chloride 1:2 0.5% 350 62.5 Embodiment 50 Copper nitrate + nickel chloride 1:3 0.5% 350 60.2 Embodiment 51 Copper nitrate + nickel chloride 1:2 0.5% 200 42.6 Embodiment 52 Copper nitrate + nickel chloride 1:2 0.5% 300 52.8 Embodiment 53 Copper nitrate + nickel chloride 1:2 0.5% 400 53.6 Embodiment 54 Copper nitrate + nickel chloride 1:2 0.5% 600 48.8 Comparative Example 5 Nickel chloride / 0.5% 350 40.8

[0089] From the results in Table 5, it can be seen that comparative example 5 is only applicable to nickel chloride prepared as a metal solution. The Ni-loaded alumina catalyst prepared by the pH adjustment method has a significantly lower CO2 conversion rate than that of Examples 45-54. The addition of dual-active metals increases the catalytic sites for carbon dioxide reduction, thereby increasing the carbon dioxide conversion rate. From the results of comparative example 31 and Examples 45-50, it can be seen that the addition of nickel chloride introduces Ni metal into the pore size of mesoporous alumina. The strong reducing property of Ni metal can effectively combine with CO2 gas molecules, and the synergistic effect of Cu metal and Ni metal is used to treat carbon dioxide waste gas. Compared with mesoporous alumina loaded with metal zinc and metal magnesium, it shows a significantly improved carbon dioxide conversion rate. From Examples 49-50, it can be seen that with the increase of Ni metal mass, the Ni metal can be used to treat the carbon dioxide waste gas. , the conversion of carbon dioxide first increases and then decreases, and the excess Ni metal agglomerates itself, reducing the catalytic activity; the results of Examples 45 and 51-54 show that with the increase of the reaction temperature, the carbon dioxide conversion rate of the system shows a trend of first increasing and then decreasing. Since CO2 methanation is a strongly exothermic reaction, untimely heat dissipation will lead to the formation of hot spots on the catalyst, thereby causing the sintering of the active component nickel, reducing the CO2 conversion rate. At the same time, high temperature conditions are conducive to the reverse water gas shift reaction, which is an endothermic reaction. Under high temperature conditions, a catalytic reaction occurs, and the CO2 conversion rate decreases; Comprehensive Table 5 results show that the dual-activity catalyst prepared using copper nitrate and nickel chloride has a CO2 conversion rate of 99.8% at 350°C, showing a significantly improved carbon dioxide methanation reaction conversion rate.

[0090] Examples 55-63 were prepared according to the preparation method and parameter conditions of Example 31, with the differences shown in Table 6.

[0091] Comparative Example 4 The preparation method and parameter conditions of Example 31 were referred to, except that only Cu was used to load alumina.

[0092] Comparative Example 5 The preparation method and parameter conditions of Example 31 were referred to, except that only Ni was used to load alumina.

[0093] Comparative Example 6 The preparation method and parameter conditions were referred to Example 31, except that no metal-loaded alumina was added.

[0094] Example 64 COS hydrolysis conversion performance

[0095] The alumina catalysts prepared in Examples 55-63 and Comparative Examples 4-6 were added to a COS catalytic hydrolysis device. In the experiment, the initial COS raw gas consisted of N2 and COS. After the gas entered the gas mixing tank, it was evenly mixed. The catalyst was located inside the quartz tube. The reaction temperature was 60-100°C under normal pressure. The gas flow rate was changed to adjust the space velocity, and the space velocity range was 6000-10000 / h. The outlet gas was collected in a gas sampling bag and sent to a gas chromatograph for analysis after passing through the sampling bag. The COS hydrolysis conversion rate after 6 hours of reaction is shown in Table 6.

[0096] Table 6 COS hydrolysis conversion performance of Examples 55-63 and Comparative Examples 4-6

[0097] Example Metal salt mass ratio Reaction temperature / ℃ Airspeed range COS hydrolysis conversion rate Embodiment 55 1:1 80 8000 / h 99.7 Embodiment 56 1:2 80 8000 / h 96.2 Embodiment 57 2:1 80 8000 / h 94.8 Embodiment 58 1:1 60 8000 / h 90.2 Embodiment 59 1:1 70 8000 / h 95.5 Embodiment 60 1:1 100 8000 / h 78.8 Embodiment 61 1:1 80 6000 / h 99.5 Embodiment 62 1:1 80 9000 / h 99.6 Embodiment 63 1:1 80 10000 / h 99.7 Comparative Example 4 / 80 8000 / h 90.4 Comparative Example 5 / 80 8000 / h 93.2 Comparative Example 6 / 80 8000 / h 78.5

[0098] From the results in Table 6, it can be seen that the COS hydrolysis conversion efficiency of Comparative Example 6 without adding a metal-loaded alumina catalyst can reach more than 75%. Since the catalytic hydrolysis of COS is an alkali-catalyzed reaction, and the surface of mesoporous alumina has alkaline groups, which can provide -OH groups to adsorb surrounding water molecules, COS molecules will react with the -OH groups on the catalyst surface by ion dipole interaction, thereby being adsorbed on the catalyst surface. Subsequently, the COS molecules react catalytically with the water molecules on the catalyst surface under the action of Cu / Ni metal, thereby causing a COS hydrolysis reaction. Comparative Examples 4-5 have increased reaction activity due to the addition of alkaline metals, but still exhibit poor COS hydrolysis conversion rates relative to Examples 55-63 using dual-active metal-loaded Cu / Ni alumina catalysts. It can be seen from the results of Examples 55-57 that when the mass ratio of Cu to Ni is maintained at 1:1, the alumina catalyst has a higher COS hydrolysis conversion rate; it can be seen from the results of Examples 55 and 58-60 that with the increase of the reaction temperature, the COS hydrolysis conversion rate shows a trend of first increasing and then decreasing. When the temperature is high, the conversion rate can reach 99% at the beginning of the reaction, but as time goes on, the conversion rate gradually decreases. When the temperature is maintained at 80°C, the COS hydrolysis conversion rate can be maintained above 95%. This may be because higher temperatures are not conducive to the desorption of H2S, resulting in the covering of the active sites of the catalyst and reducing the catalytic hydrolysis effect; at lower temperatures, the speed at which H2S moves in the mesoporous channels is slower, resulting in its adsorption and activation. The active sites are covered and the conversion rate decreases; it can be seen from the results of Examples 55 and 61-63 that the air velocity reflects the time that the gas stays on the catalyst, and the larger the reaction air velocity, the greater the gas flow rate; the increase in air velocity has little effect on the COS hydrolysis conversion rate, but with the increase in air velocity, the contact time between COS and the catalyst becomes shorter, and the catalytic hydrolysis efficiency gradually decreases with time. When the air velocity is 6000 / h, although the contact time between the catalyst and COS is longer and the reaction is more sufficient, the reduction in gas flow rate will cause the catalytic hydrolysis product H2S to cover the reactive sites, which is not conducive to the subsequent reaction; and when the air velocity is 8000 / h, the gas flow rate is larger, which is more conducive to the escape of H2S and reduces the possibility of the reactive sites being covered by it. Based on the results of Table 6, the Cu / Ni-loaded alumina catalyst prepared using copper nitrate and nickel chloride has a COS hydrolysis conversion rate of 99.7 at 80°C and an air velocity of 8000 / h, showing a significantly improved hydrolysis conversion performance of carbonyl sulfide.

[0099] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.

Claims

1. A method for preparing a dual-activity catalyst based on an alumina framework, characterized in that: The dual-activity catalyst comprises mesoporous alumina and a metal salt: The preparation method of the mesoporous alumina comprises the following steps: The template agent is added to ethanol, and stirred at 200 rpm for 10 minutes to fully dissolve it to obtain a solution; an acid regulator is added to the solution, the pH is adjusted to 0.28-0.42, and the mixture is evenly mixed to obtain an acidic solution; aluminum isopropoxide is added to the acidic solution, and the solution is placed in an ultrasonic cleaner to fully dissolve it to obtain a sol; the sol is placed in a vacuum drying oven at 60-90° C. and dried for 24 hours to obtain a dry material; the dry material is ground into powder, and after grinding, the powder is placed in a box-type resistance furnace and heated to 400-700° C., and the powder is calcined at a constant temperature for 6 hours, and then cooled to room temperature to obtain the mesoporous alumina; The dual-activity catalyst is prepared by a pH adjustment method, and the preparation method comprises the following steps: Dissolving a metal salt in an ammonia solution to obtain a metal salt solution; adjusting the pH value of the mixed solution of the metal salt solution to 12 using concentrated ammonia water to obtain an alkaline solution; adding the mesoporous alumina to the alkaline solution, placing it in an oscillator and oscillating it at room temperature for 2 hours to obtain a mixture; washing and filtering the mixture for multiple times, and vacuum drying it at 100° C. for 12 hours to obtain a dry body; reducing the dry body with a reducing gas at a flow rate of 50 mL / min, a temperature of 550° C., and a time of 8 hours to obtain the dual-activity catalyst; The mass ratio of the template to aluminum isopropoxide is 1:4; The template is selected from silicon-containing templates; The silicon-containing template is synthesized by emulsifying butyl methacrylate, KH-570 and tetradecyl acrylate to initiate polymerization; The mass ratio of the metal in the dual-activity catalyst to the mesoporous alumina is 0.001-0.007:1; The acid regulator is selected from nitric acid; The metal salt is selected from a mixture of copper nitrate and nickel chloride; the mass ratio of the copper nitrate to the nickel chloride is 1-3:1-3.

2. An application of a dual-activity catalyst based on an alumina framework prepared by the method of claim 1, characterized in that: The dual-activity catalyst is used in the exhaust gas catalytic reaction, wherein the exhaust gas catalytic reaction includes catalytic denitration reaction, carbon dioxide methanation reaction, and COS hydrolysis catalysis; in the catalytic denitration reaction, the metal salt is selected from a mixture of copper nitrate and nickel chloride in a mass ratio of 2:1; the metal loading is 0.5%; and the reaction temperature is 300°C.

3. The use according to claim 2, characterized in that: In the carbon dioxide methanation reaction, the metal salt is selected from the copper nitrate and the nickel chloride mixed in a mass ratio of 1:2; the metal loading is 0.5%; and the reaction temperature is 350°C.

4. The use according to claim 2, characterized in that: In the COS hydrolysis catalysis, the metal salt is selected from the copper nitrate and the nickel chloride mixed in a mass ratio of 1:1; the metal loading is 0.5%; the reaction temperature is 80° C., and the space velocity is 8000 / h.

Citation Information

Patent Citations

  • Hydrolyst for COS and CS2 and application thereof

    CN100431668C

  • CHA-type zeolite and production method therefor

    CN109195911A

  • Method for denitrifying NO by directly decomposing NO catalytically by using supported metal oxide catalyst

    CN104474890A